2012
DOI: 10.1016/j.ijporl.2012.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing toddlers’ speech-sound discrimination

Abstract: Objective Valid and reliable methods for assessing speech perception in toddlers are lacking in the field, leading to conspicuous gaps in understanding how speech perception develops and limited clinical tools for assessing sensory aid benefit in toddlers. The objective of this investigation was to evaluate speech-sound discrimination in toddlers using modifications to the Change/No-Change procedure1. Methods Normal-hearing 2- and 3-year-olds’ discrimination of acoustically dissimilar (“easy”) and similar (“… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 69 publications
4
43
0
Order By: Relevance
“…No feedback was provided on test trials; rather, a puzzle piece appeared on the screen to help keep track of progress and to provide reinforcement. These puzzles had fewer pieces than those shown to adults (10 vs. 30) because in previous work (Holt & Carney, 2007;Holt & Lalonde, 2012;Lalonde & Holt, 2014), we found that children were reinforced by the puzzle activity and liked guessing what picture the puzzle was forming. Children also received noncontingent verbal praise.…”
Section: Taskmentioning
confidence: 46%
See 3 more Smart Citations
“…No feedback was provided on test trials; rather, a puzzle piece appeared on the screen to help keep track of progress and to provide reinforcement. These puzzles had fewer pieces than those shown to adults (10 vs. 30) because in previous work (Holt & Carney, 2007;Holt & Lalonde, 2012;Lalonde & Holt, 2014), we found that children were reinforced by the puzzle activity and liked guessing what picture the puzzle was forming. Children also received noncontingent verbal praise.…”
Section: Taskmentioning
confidence: 46%
“…The training phase was the same for 3-and 4-year-olds, except that a more lenient training criterion was used for the younger children. Consistent with similar studies (Holt & Lalonde, 2012;Lalonde & Holt, 2014;Trehub, Schneider, & Henderson, 1995), 3-year-olds were required to complete five trials in a row correctly to move on to the testing phase (rather than 18 of the last 20 training trials). Additional forms of reinforcement were integrated into the testing phase.…”
Section: Taskmentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, researchers have highlighted the lack of behavioral measures available to test speech perception in pre-school-age children Vance et al 2009;Holt & LaLonde 2012). Advances are being made in electrophysiological methods of perception assessment (e.g., Weber et al 2005), but these methods are expensive and out of range of the average researcher or clinician.…”
Section: Introductionmentioning
confidence: 99%